2011
DOI: 10.1097/ta.0b013e31820329d8
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Injection of Mesenteric Lymph Produced During Hemorrhagic Shock Decreases RBC Deformability in the Rat

Abstract: Objective To test the hypothesis that gut-derived factors carried in trauma-hemorrhagic shock (T/HS) lymph are sufficient to induce red blood cells (RBC) injury, to investigate their potential mechanisms of action, and to define the time post-T/HS that these factors appear in the lymph. Methods Mesenteric lymph collected from T/HS or trauma-sham shock (T/SS) rats over different time periods was injected intravenously into male rats at a rate of 1 mL/h for 3 hours. RBC deformability was measured using laser-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…CPSI-121, a guanylhydrazone-derived compound, has been shown to result in efferent vagal fiber activation after systemic administration and thus can be used to provide VNS through pharmacologic means [33]. While the exact therapeutic window is unknown, VNS appears to have the greatest benefit 1–2 hours following injury [10, 63]. Given the greater clinically feasibility of administering a pharmacologic agent over direct, electrical stimulation of the vagus nerve, pharmacologic VNS is an attractive option that may yield higher therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CPSI-121, a guanylhydrazone-derived compound, has been shown to result in efferent vagal fiber activation after systemic administration and thus can be used to provide VNS through pharmacologic means [33]. While the exact therapeutic window is unknown, VNS appears to have the greatest benefit 1–2 hours following injury [10, 63]. Given the greater clinically feasibility of administering a pharmacologic agent over direct, electrical stimulation of the vagus nerve, pharmacologic VNS is an attractive option that may yield higher therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Newer theories have focused on the mesenteric lymph (ML) as the inciting source for the development of SIRS [2, 9]. These theories propose that pro-inflammatory mediators are produced in the gut after trauma, which can be released into the systemic circulation via the ML to cause and propagate the systemic inflammatory response [2, 10, 11]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Condon et al demonstrated that intravenously injected mesenteric lymph produced during hemorrhagic shock decreased RBC deformability in the rat [276]. The in vivo inhibition of inducible nitric oxide synthase (iNOS) did not prevent lymph-induced RBC injury.…”
Section: The Major Determinants Of Rbc Deformabilitymentioning
confidence: 99%
“…37 Postshock mesenteric lymph may be toxic through a variety of mechanisms, including endothelial inflammation, 6,26 neutrophil priming, 38,39,40 enhanced apoptosis, 41 pulmonary epithelial inflammation, 42 and RBC hemolysis. 43,32 In this study, we demonstrate that postshock mesenteric lymph is necessary and sufficient to provoke ALI in the naïve rat. These data further support a central mechanistic role of PSML in the pathogenesis of ALI.…”
mentioning
confidence: 96%